Does Internet Usage Lead to An Increase in Household Incomes? Indonesian Rural Case Study - Priyatna, M. Fahmi (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2022)
This study analyzes the effect of internet utilization on household income in rural Indonesia using Sakernas 2018 data. This research uses propensity score matching (PSM) to achieve the research objectives. The results show that the probabilities of using the internet are caused by family size, age of the head of the household, work experience, marital status, formal and informal education, experiencing severe difficulties in bodily functions, gender, business sector, and financial management. Furthermore, the study finds that the internet utilization increases household income in rural Indonesia by 29 percent.